Linkage types, hydrocarbons and their relationship with subsurface fault zones width and displacement scaling - Cui, Lijie; Zhang, Pan; Niu, Yuxi; Huang, Yawen; Chen, Zening (Frontiers in Earth Science, 2025)
The width-displacement (W-D) relationship of fault zones is significant for deepening the understanding of subsurface faulting mechanisms, yet quantitative research using seismic reflection data, especially for boundary identification, remains challenging. This study focuses on the quantitative characterization of the W-D relationship in fault zones using 3D seismic data from the C36 Prospect in the Junggar Basin, China. The hybrid attributes derived from several conditioning approaches, multiple-attribute calculation, and a supervised artificial neural network (ANN) have effectively enhanced images of the fault zones. Quantitative analysis using the computed hybrid attributes reveals that the center and the bend positions of the single fault zone respectively control the largest width and displacement values. Different fault sets containing different fault linkage types with different geometry, standing for different evolution stages, provide various contributions to the W-D relationship, leading to the different scatter data distribution. This research clarifies the relationship between the evolution of fault zones and the scatter data, offering new insights into the mechanisms controlling hydrocarbon accumulation and providing valuable guidance for future exploration.